The electrocardiographic manifestations of athlete`s heart and their association with exercise exposure - Bessem, B.; De Bruijn, M. C.; Nieuwland, W.; Zwerver, J.; Van Den Berg, M. (European Journal of Sport Science, 2018)
Objective: The aim of this study was to define the minimum amount of exercise per week (`current exposure`) and the total amount of exercise (`lifetime exposure`) needed to lead to the electrocardiographic changes fitting athlete`s heart. Methods: All the pre-participation screenings (including electrocardiograms (ECGs)) from collegiate athletes performed at University Sports Medical Center in 2013 and 2014 were collected. Data on height, weight, sex, age, current sport(s) participation and lifetime sport(s) participation were collected. Current exposure was categorised into 0-3, 3-6, 6-10 and >10 hours/week. Lifetime sport exposure was divided into five categories: 0-1000, 1001-2000, 2001-3000, 3001-4000 and >4000 hours. Results: The study population consisted of 1229 athletes (current exposure) and 1104 athletes (lifetime exposure). Current sport exposure: There was a significant increase in training-related ECG changes in the category 3-6 vs. <3 hours/week. When looking at individual parameters, we found an association with a significant difference in sinus bradycardia and QRS voltage (<3 vs. 3-6 hours/week) and first-degree AV-block (<3 vs. >10 hours/week).Lifetime sport exposure: There was an increase in training-related ECG changes that reached significance at an exposure >3000 hours. When looking at individual parameters, we found an association with a significant difference in sinus bradycardia (0-1000 vs. 2001-3000), QRS voltage (0-1000 vs. 3001-4000) and first-degree AV-block (0-1000 vs. >4000). Conclusion: A minimum of =3 hours/week of current exposure and a lifetime exposure of >3000 hours is needed to lead to the electrocardiographic changes fitting athlete`s heart.